Decision Support System Design for Wedding Organizer Tradeshow Selection using AHP and TOPSIS - Rayinda Pramuditya Soesanto; Afrin Fauzya Rizana (International Journal of Innovation in Enterprise System, 2021)
Wedding organizers, as one of the creative industries, often participate in a trade show as one of the marketing mediums. Many wedding-related trades show events are held every year. But the cost to participate in one trade show event is quite expensive and increases from time to time. Thus, before deciding to participate in a trade show, it is important to evaluate whether the trade show events are recommended to join or not. The purpose of this study is to design a decision support system that will help the wedding organizer to decide their participation in a trade show. The decision model was constructed using AHP and TOPSIS methods. There are seven factors considered in the model, i.e., tradeshow location, reputation and professionalism of the organizer, cost estimation, trade show prestige, tenant reputation, time of the event, the attractiveness of the event. By using the AHP method, the priority weight of each factor was calculated. Moreover, the weight obtained will be used in developing a decision model combined with the TOPSIS method. The decision support system was developed afterward by using the SCRUM method. The feature of the system is discussed in the paper.